3, 4-Di-O-Caffeoylquinic Acid Inhibits Angiotensin-II-Induced Vascular Smooth Muscle Cell Proliferation and Migration by Downregulating the JNK and PI3K/Akt Signaling Pathways. (18th June 2011) - Chiou, Wen-Fei; Chen, Chien-Chih; Wei, Bai-Luh
Abstract : We previously reported 3, 4-di- O -caffeoylquinic acid (CQC) protected vascular endothelial cells against oxidative stress and restored impaired endothelium-dependent vasodilatation. Here, we further investigated its anti-atherosclerotic effect against angiotensin II (Ang II) evoked proliferation and migration of cultured rat vascular smooth muscle cells (rVSMC). The results showed CQC (1–20 μ M) clearly inhibited Ang-II-stimulated BrdU incorporation and cell migration of rVSMC in a concentration-dependent manner but without significant cytotoxicity. Western blot analysis revealed Ang II increased the phosphorylation levels of Akt and mitogen-activated protein kinases (MAPKs;p38, ERK1/2 and JNK) in rVSMC. In the presence of phosphatidylinositol 3-kinase (PI3K) inhibitor wortmannin and three individual MAPK inhibitors SB203580, PD98059 and SP600125, both Ang-II-induced cell proliferation and migration were significantly attenuated, although to differing extents, suggesting the PI3K and MAPK signal pathways all participated in regulating rVSMC proliferation and migration. Also, the CQC pretreatment markedly suppressed Ang-II-induced phosphorylation of Akt and JNK rather than ERK1/2, although it failed to affect p38 phosphorylation. In conclusion, our data demonstrate CQC may act by down-regulating Akt, JNK and part of the ERK1/2 pathways to inhibit Ang-II-induced rVSMC proliferation and migration. The anti-atherosclerotic effect of CQC is achieved either by endothelial cells protection or by VSMC proliferation/migration inhibition, suggesting this compound may be useful in preventing vascular diseases.